2007
DOI: 10.1152/japplphysiol.00524.2007
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral microdialysis of gabazine in the dorsal medulla reverses thermal prolongation of the laryngeal chemoreflex in decerebrate piglets

Abstract: The laryngeal chemoreflex (LCR) is elicited by water in the larynx and leads to apnea and respiratory disruption in immature animals. The LCR is exaggerated by the elevation of brain temperature within or near the nucleus of the solitary tract (NTS) in decerebrate piglets. Thermal prolongation of reflex apnea elicited by superior laryngeal nerve stimulation is reduced by systemic administration of GABA(A) receptor antagonists. Therefore, we tested the hypothesis that microdialysis within or near the NTS of gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
5
28
0
Order By: Relevance
“…Another aspect of our experimental LCR maneuvers that distinguish them from naturally occurring apneas is that the animals are continuously ventilated and so do not become hypoxic or hypercapnic during the periods of phrenic “apnea”. We found in this study and have found in previous studies somewhat variable effects of drug or changes in body temperature on respiratory frequency (Curran et al, 2005; Xia et al, 2007a, b). It is worth noting that, to the extent an increased respiratory frequency represents an increased respiratory drive, such an increase in frequency would tend to decrease, rather than increase the duration of apnea and the LCR.…”
Section: Discussionsupporting
confidence: 81%
“…Another aspect of our experimental LCR maneuvers that distinguish them from naturally occurring apneas is that the animals are continuously ventilated and so do not become hypoxic or hypercapnic during the periods of phrenic “apnea”. We found in this study and have found in previous studies somewhat variable effects of drug or changes in body temperature on respiratory frequency (Curran et al, 2005; Xia et al, 2007a, b). It is worth noting that, to the extent an increased respiratory frequency represents an increased respiratory drive, such an increase in frequency would tend to decrease, rather than increase the duration of apnea and the LCR.…”
Section: Discussionsupporting
confidence: 81%
“…The LCR is developmentally regulated and occurs more commonly in newborn human infants and animals compared to adults (42, 148, 149). The LCR has long been suspected to be a cause of or a contributing factor in some SIDS cases; investigators hypothesize that infants during the susceptible age range aspirate gastric contents during sleep and thereby trigger this reflex, which, if prolonged or unchecked, leads to lethal apnea (148–151). In anaesthetized piglets, the nonspecific inhibition of all neurons in the rostral medullary raphé (by focal dialysis of the GABA A receptor agonist muscimol) causes a prolonged duration of apnea in the LCR (152).…”
Section: The Function Of the Medullary 5-ht System And Its Relationshmentioning
confidence: 99%
“…In piglets, the hyperthermic exaggeration of the LCR is most striking under postnatal day 5 and disappears by postnatal day 20 (151). Intravenous infusion of GABA A receptor blockers reverses the enhancement of laryngeal apnea by whole-body hyperthermia, suggesting that the effect of hyperthermia on the LCR is mediated by GABAergic inhibition of respiration (151a). The specific role of medullary 5-HT neurons in modulation of the LCR in early life is under investigation.…”
Section: The Function Of the Medullary 5-ht System And Its Relationshmentioning
confidence: 99%
“…The enhancement of laryngeal apnea by hyperthermia was first demonstrated by Haraguchi and associates, who found that the threshold for laryngeal adductor contraction during SLN stimulation was greatly reduced by hyperthermia in puppies, but much less so in adult dogs (Haraguchi et al, 1983). More recently, we have shown that the duration of the LCR–both the respiratory disruption and the associated apnea–following water injection into the laryngeal lumen is prolonged by hyperthermia in decerebrate neonatal piglets (Curran et al, 2005; Xia et al, 2008a; Xia et al, 2007; Xia et al, 2006) and anesthetized rat pups (Xia et al, 2008b). The enhancement of the reflex appears to depend on a temperature-sensitive mechanism in or near the nucleus of the solitary tract (Xia et al, 2006) and can be reversed by pharmacological blockade of GABA A receptors in the same region (Xia et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that in neonatal piglets and rat pups, the respiratory disruption associated with the LCR is greatly exaggerated in animals that are warmed 1–3 °C above their normal body temperatures (Curran et al, 2005; Xia et al, 2008a; Xia et al, 2007; Xia et al, 2006; Xia et al, 2008b). This effect of hyperthermia is reversible by returning the body temperature to normal.…”
Section: Introductionmentioning
confidence: 99%